Taxonomy of the genus Microichthyurus Pic (Coleoptera, Cantharidae, Chauliognathinae), with descriptions of nine new species from China - Hanqing Lin; Haoyu Liu; Xingke Yang; Yuxia Yang (Deutsche Entomologische Zeitschrift)
The genus Microichthyurus Pic, 1919, from China and its adjacent areas is reviewed. M. robusticeps Pic, 1923 (Laos and Vietnam), is redescribed. Nine new species are described from southern China, including M. falcatus sp. nov., M. quadratus sp. nov., M. crassicornis sp. nov., M. niger sp. nov., M. tertius sp. nov., M. guangxiensis sp. nov., M. flavipennis sp. nov., M. bimaculatus sp. nov., and M. strictipennis sp. nov. These species are illustrated with habitus and genital segments of both sexes, as well as aedeagi. Four species groups are defined, and each is provided with a key for species identification and a distribution map.